American pie [videorecording (DVD)] - Biggs, Jason, 1978-; Klein, Chris, 1979-; Elizabeth, Shannon, 1973-; Hannigan, Alyson, 1974-; Lyonne, Natasha; Scott, Seann William; Nicholas, Thomas Ian; Reid, Tara, 1975-; Suvari, Mena, 1979-; Thomas, Eddie Kaye, 1980-; Levy, Eugene, 1946-; Weitz, Paul, 1966-; et al. (Universal, 2002)
Follows the hapless adventures of four "unlucky in love" high school friends as they gear up for the prom.